A comparative study: Students' process skills and students' analytical thinking with learning models - Kamid, Kamid; Kurniawan, Dwi Agus; Rahman, Adriyan Ardi (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
The purpose of this study was to find out a comparison of students' process skills with students' analytical thinking with the learning model at Batang Hari Middle School on student perceptions to determine the relationship of learning models to students' analytical thinking skills in Mathematics and to find out the relationship between learning models and process skills. The method used in this study is a quantitative method with a comparative type. The results of the description test can be concluded that one SMP in Batang Hari is superior to the others. Based on the results of the t-test, it can be concluded that there is a comparison between the thinking and processing skills of students using the STAD learning model. The correlation test results show a relationship between the learning model and the process skills and analytical thinking of Batang Hari Junior High School students.